Reductions in positive Clostridioides difficile events reportable to National Healthcare Safety Network (NHSN) with adoption of reflex enzyme immunoassay (EIA) testing in 13 Atlanta hospitals - Goodenough, Dana; Sefton, Samantha; Overton, Elizabeth; Smith, Elizabeth; Kraft, Colleen S.; Varkey, Jay B.; Fridkin, Scott K. (Infection control and hospital epidemiology, 2022)
In total, 13 facilities changed C. difficile testing to reflexive testing by enzyme immunoassay (EIA) only after a positive nucleic acid-amplification test (NAAT); the standardized infection ratio (SIR) decreased by 46% (range, −12% to −71% per hospital). Changing testing practice greatly influenced a performance metric without changing C. difficile infection prevention practice.